The Impact of Social Media Marketing and Lifestyle on Visit Decisions: The Mediating Role of the Millennial Generation - Junipriansa, Donni; Disastra, Ganjar Mohamad (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: The coffee shop trend in Bandung is growing, with an increasing number of establishments intensifying competition, as many cafes offer unique features to distinguish themselves from competitors. This study examined the interrelationships among social media marketing, lifestyle, the millennial generation, and the decision to visit cafes.Design/Methodology/Approach: This quantitative study collected data from 100 Bandung cafe visitors via Likert-scaled online questionnaires, utilizing simple random sampling. The data were then analyzed using SEM-PLS in SmartPLS 4.Research findings: All proposed hypotheses were supported. The findings indicate that both social media marketing and lifestyle significantly influence the decision to visit cafes. The millennial generation mediates the enhancing effect of social media marketing and lifestyle on visit decisions.Theoretical Contribution/Originality: The millennial generation effectively mediates how social media marketing and lifestyle jointly influence visit decisions. Moreover, this study proposes alternative dimensions for measuring social media marketing, lifestyle, the millennial generation, and visit decisions.Practitioners/Policy Implications: Cafe managers in Bandung should improve the quality of their social media marketing content and develop a deeper understanding of generational lifestyle differences. Such insights can provide a clearer perspective and support the formulation of more effective marketing strategies and tactics.Research Limitations/Implications: This study focused on visit decisions influenced by social media marketing, lifestyle, and the millennial generation. Future research could benefit from incorporating other key factors, such as cafe branding or experiential marketing, to provide a more comprehensive understanding. Future studies should expand their scope to a broader geographic area, such as the provincial level.